Genetic structure in cultivated quinoa (Chenopodium quinoa Willd.), a reflection of landscape structure in Northwest Argentina - Costa Tártara, S. M. (2012)
Fil: Costa Tártara, S. M. Instituto Nacional de Tecnología Agropecuaria (INTA). Centro de Investigación de Recursos Naturales (CIRN). Hurlingham, Buenos Aires, Argentina.